ADVERTISING ACTIVITY: SOCIAL MEANING OF MODERN SOCIETY - Atashkadeh (Аташкаде Руслана Вадимівна), Ruslana; Honcharenko (Гончаренко Марина Михайлівна), Maryna; Puhach (Пугач Анастасія Вікторівна), Anastasiia; Sierova (Сєрова Юлія Володимирівна), Yuliia (Politology bulletin, 2022)
The article attempts a socio-philosophical analysis of advertising activity as a factor of socio-cultural changes in society and the formation of social meanings. The concept of advertising appears to indicate a peculiar nature of human economic activity at the level of consumption. it is stated that advertising is not only a means of communication (the product of objective conditions), but also the affirmation and deployment of the activity of a social subject. It was determined that advertising is a branch of communication and a social phenomenon that represents the information space where the reality of consumption of declared values is cultivated.It was revealed that, by its essence, advertising activity is a polyphonic phenomenon, diversified in many forms. In such a polyphony of advertising activity, what is dominant is what appears through the relationship between what is individually desired and what is socially acceptable. The functionality of such a relationship is ensured by appropriate mass media and the multidimensionality of advertising itself.It has been proven that advertising activity allows not only to outline these orientations in a unique way through the innovative use of symbols, metaphors, «simulacrums», etc., but also to determine the main directions of intensification of the life activity of a person and society thanks to the reorganization and transformation of social relations.

У статті здійснюється спроба соціально-філософського аналізу рекламної діяльності, як чинника соціокультурних змін в суспільстві та формування соціальних смислів. Поняття реклами з’являється для позначення своєрідного характеру економічної діяльності людини на рівні споживання. зазначено, що реклама є не тільки засобом комунікації (породженням об’єктивних умов), але й утвердженням та розгортанням діяльності соціального суб’єкта. Визначено, що реклама — це галузь комунікації і соціальний феномен, який репрезентує інформаційний простір, де культивується реальність споживання задекларованих цінностей.Виявлено, що за своєю сутністю рекламна діяльність є поліфонічним явищем, урізноманітненим багатьма формами. У такій поліфонії рекламної діяльності домінантним є те, що постає через відношення індивідуально бажаного та соціально прийнятного. Функціональність такого відношення забезпечується відповідними засобами масової інформації та багатовимірністю самої реклами.Доведено, що рекламна діяльність дозволяє не тільки своєрідно окреслити ці орієнтири через інноваційне використання як символів, метафор, «симулякрів» тощо, але й визначити основні напрямки інтенсифікації життєдіяльності людини і суспільства завдяки реорганізації, трансформації соціальних відносин.
РЕКЛАМНА ДІЯЛЬНІСТЬ: СОЦІАЛЬНІ СМИСЛИ СУЧАСНОГО СУСПІЛЬСТВА
Keywords: advertising; advertising activity; social meanings; information space; society; реклама; рекламна діяльність; соціальні смисли; інформаційний простір; суспільство